Ketamine-associated upper urinary tract dysfunction: What we know from current literature - Zhihuan Zheng; Zhongyi Li; Jiazhe Yuan; Feng Han; Li Huang; Zhao Wang (Asian Journal of Urology)
Objective: To review the current literature on ketamine-associated upper urinary tract (UUT) dysfunction and provide an overview of its pathogenesis and treatment principles. Methods: A literature search was conducted using PubMed and Cochrane databases for relevant articles published in English between 2008 and 2023. Keywords used included “ketamine” and “upper urinary tract”. Results: A total of 22 papers were included. Relatively few studies have focused on ketamine-associated UUT dysfunction. Exclusion criteria included lack of hydronephrosis, or pathological findings. After careful screening and exclusion, we finally adopted 11 of these papers and analyzed them. Ketamine-associated UUT dysfunction may be a concern in this field. Conclusion: Ketamine abuse can lead to UUT impairment and dysfunction, with symptoms such as bladder dysfunction and contracted bladder with vesicoureteral reflux, direct damage and barrier dysfunction, inflammation, apoptosis, fibrosis and stricture, and papillary necrosis. Oxidative stress, autophagy, and microvascular injury are also potential pathogenic mechanisms. The detection of these symptoms largely depends on laboratory and imaging examinations. The treatment principles of ketamine-associated UUT dysfunction are protecting the UUT, improving bladder dysfunction, and resuming normal social life. More investigations are needed to clarify the mechanisms and shed light on the treatment of ketamine-associated UUT damage.